Pringle`s Maneuvre: A maneuvre beyond its time - Fonseca Neto, Olival Cirilo Lucena da; Mesquita, Maria Eduarda (Brazilian Journal of Transplantation, 2021)
Introduction: Pringle maneuver is a widely used surgical technique in hepatic ressections, consisting of blood inflow occlusion of porta hepatis, reducing intraoperative bleeding and having as alternative a selective hemi-hepatic vascular occlusion. However, this maneuver results in ischemia-reperfusion injury, and some studies associate it to higher morbidity and mortality, besides of posing a possible increased risk for malignant progression. A search was performed in the PubMed database using the descriptor "Pringle Maneuver". Four retrospective studies and a prospective study were analyzed comparing blood loss, need for blood transfusion, time of surgery, complications, time of diseasefree survival, and overall survival of patients diagnosed with hepatocellular carcinoma (CHC) submitted to resections whether using or not Pringle maneuver. Studies assessing the superiority of selective hemi-hepatic occlusion compared to Pringle Maneuver present conflicting results. Therefore, by considering the relevance of bleeding control in liver resections, further studies on the subject are needed in order to build a solid scientific evidence.